Multi-Watt-level 3.28-3.45 μm difference frequency generation using synchronous fiber lasers - Murray,RT; Runcorn,TH; Kelleher,EJR; Taylor,JR (2016)
We report multi-Watt-level average power 3.28-3.45 μm difference frequency generation using two sychronous picosecond master oscillator power fiber amplifiers. Greater than 3.4 W of idler power is generated across the entire spectral tuning range.